Representation of Women’s War Experiences in Femi Osofisan’s Morountodun and Women of Owu - SESAN, Azeez Akinwumi (Anafora, 2023)
The history of wars in Yoruba nationalities reveals different experiences and challenges faced by women in times of war. In some social, historical, and literary texts, women have been presented as the primary cause of some of these wars. Yet, in a few of these texts, women have also been presented as the harbingers and brokers of peace during catastrophic Yoruba wars, or as their victims and heroines. This paper analyses the fate and status of women in Yoruba historical wars in Femi Osofisan’s Morountodun (1999) and Women of Owu (2011). It argues that the two plays present the collective and individual experiences of women, respectively. On the one hand, the characterisation of Titubi and Moremi in Morountodun valorises the heroic deeds of women during various wars and these heroic women’s efforts to restore peace and order in their respective communities. On the other hand, in Women of Owu, women are presented as the vulnerable group in fratricidal and catastrophic wars caused by male egotism. Osofisan’s plays, therefore, encompass a range of diverse, oftentimes contradictory, positions, experiences, and roles embraced by women in war situations.